A report on practice in industry training in marine fisheries. - Gastador, Conrado S. (College of Fisheries, University of the Philippines, 1961)
The Philippines with its coastline or shoreline, inland lakes and waters and bays is among the leading nations of the world concerned much of her commercial fishing industry. With the presence of several thousand of species of fish in our waters. It is said to be the fisherman's eden, if we would only employ various methods and technique of catching fish in the most scientific way. In so far as fishing in the Philippines is concerned. We Filipinos are far behind than that of other countries, in respect to the use of modern and mechanized methods of fishing. However as time goes by or a year from now, it is believe that we can attain the modernization and mechanization of our various local methods of fishing little by little in order to give initiative to our fishermen. Today, fishing in the Philippines is solely a vocation for a man, a means of livelihood, but in some years to come this industry will prosper, and it can boast to the whole world basing the geographical location we have in a good fishing ground and we cannot import fish from other countries anymore. It is our primary concern to utilize and conserve our vast natural resources in the sea and these resources in the sea and in this can attained by using legal techniques of fishing, So our fishery resources will not have a chance to depleted. This report constitutes the description of the different fishing gears commonly used in the Philippines. Included herein is the operations, methods of constructions of the gear aforementioned during my 4 moths practice-in-industry training in fish capture.